Risk factors related to anterior cruciate ligament injury of female basketball players during stepping movements - Lee, H. -J.; Tseng, T. -H.; Liang, C. -Y. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to compare the biomechanical factors related to anterior cruciate ligament injury during unanticipated movements after landing and immediately applied in stepping movements. Four healthy female basketball players were recruited in this study. All subjects were asked to perform five successful trials at each stepping movements after jump landing. Results of the current study showed that different step movements may result in different biomechanical factors to cause different ACL injury risk levels. Future studies should focus on investigating the best jump landing and stepping strategy, and analyzing better ways to coordinate lower extremity joints to reduce noncontact ACL injury risks.